SUKSESI KOMUNITAS MIKROBA PADA PROSES FERMENTASI KEFIR SUSU SAPI - Tanjung, Nadia
Kefir, a fermented beverage, is made by inoculating kefir grain which contains Lactic Acid Bacteria (LAB), Acetic Acid Bacteria (AAB), and yeast. Each microbes have different roles in the production of flavors and new grains. Therefore, a microbial succession study needs to be done as the basis for further optimizations. This study aims to determine (1) optimum inoculum concentration and incubation time of kefir by hedonistic test, (2) the total and relative microbial abudance of kefir milk and kefir grain using optimum fermentation condition. Determining optimum inoculum concentration is done by organoleptic test of the batch fermentation of three inoculum concentration variant: 5% (w/v), 7,5% (w/v), and 10 (w/v) for 36 hours of fermentation (sampling is done each 6 hours). Fermentation is done in ambiance temperature of 27oC, starting pH at 6,5, and total cow’s milk volume at 100 mL. Total and relative microbial abudance of kefir milk and kefir grain is done using the same method as previous, except for the fermentation time, which is 30 hours with each 3 hours sampling time. Enumeration is done using Total Plate Count (TPC) method in four growth mediums: GYCA for AAB, MRSA for LAB, PDA for yeast, and NA for total bacteria, followed by isolate purification, macroscopic and microscopic characteristic determination. The results of fermentation condition optimization shows that the highest organoleptic index is reached by 7,5% (w/v) variant at 18 hours fermentation, followed by 5% (w/v) variant at 24 fermention hours, and 10% (w/v) variant at 12 hours fermentation; with the organoleptic index of 4,63±0,04; 4,5±0,00; and 4,25±0,08 respectively. The total abudance of total bacteria, AAB, LAB, and yeast of kefir grain are 1×1010 CFU/g, 4×108 CFU/g, 2×108 CFU/g, and 3×107 CFU/g respectively. While in kefir milk, the trend shows that at 0-3 hours fermentation the growth rate of all microbial is slow (growth rate <0,15 CFU/mL.hour) except for AAB (growth rate = 0,24 CFU/mL.hour). After 3 hours, the trend shows cell growth until 6 hours fermentation for yeast (growth rate = 0,99 CFU/mL.hour), 9 hours for LAB (growth rate = 0,75 CFU/mL.hour), and 15 hours for total bacteria and AAB (growth rate at 0,38 CFU/mL.hour and 0,32 CFU/mL.hour respectively). After 18 hours fermentation onward, all trend has reached stagnation. There are 14 isolates that is purified from all growth medium; six is isolated from NA (isolate A, B, C, D, E, and F), three is isolated from PDA (isolate G, H, and I), another three is isolated from MRSA (isolate J, K, and L), and the last two is isolated from GYCA (isolate M and N). Population dynamics in kefir grains’ results show that the dynamics is stable at each sampling time, with the dominant isolate of each microbes are isolate M at 71,77%, isolate K at 65,20%, isolate H at 62,34%, and isolate A at 36,54%. While the population dynamics at kefir milk shows that there are changes in dynamics, although the dominant isolate stayed the same which are isolate M at 81,16%, isolate K at 64,73%, isolate H at 58,52%, and isolate A at 42,80%. The change in dynamics happened at 3 hours and 18 hours. The relative abudance of isolate G increased by 20,99% at 3 hours fermentation, while isolate L increased by 15,81% at 18 hours fermentation. From this study, it can be concluded that (1) the inoculum concentration of 7,5% (w/v) at 18 hours incubation is the optimum condition for kefir fermentation; (2) the total and relative microbial abudance in kefir grain is stable at each sampling time, while there are changes in population dynamics of kefir milk. The fermentation itself can be separated in 3 stages: adaptation stage (0-3 hours) with AAB as the dominant microbes, early fermentation stage (3-18 hours) with LAB and yeast as the responsible microbes, and late fermentation stage ( >18 hours) with AAB and yeast as the responsible microbes.